(untitled) (Damascus University Journal for engineering sciences, 2021)
This research presents an integrated approach to the design and numerical analysis of two types of artificial lumbar discs. 3D design and reverse modeling techniques offer promising tools for improving current design methods. In this study, two models were designed for ball-on-socket lumbar intervertebral discs (CHARITE´-ProDisc-L). An engineering protocol was proposed for designing the artificial disc and evaluating the mechanical properties within the interface area between the disc components. This is done with the aim of evaluating disc efficiency.. The numerical model of the two discs was produced based on the measured values from the radiographs mentioned in the previous studies. The performance of the two discs was evaluated by observing the distribution of equivalent stress values on the upper and lower endplates and the core, using 3D finite element method based on ansys v19.2. The proposed engineering approach enabled the production of personal numerical models for each patient according to the level of required implantation. The measured stresses values also indicated the areas with maximum pressure to which each disc is subjected, which requires some design modifications to obtain the optimum performance of the Artificial disc.